An Analysis of Flouting Maxims in the Podcast Psick Show Scene “Asking BTS RM on 2022 Income Tax” - Malihatunnazihah, Avira; Kustianingsih, Kustianingsih; Febrianti, Annisa Siska; Fitriana, Lutfi Faida; Malikhah, Fatatun (UM Purwokerto Press, 2025)
Grice’s conversational maxims, developed by British philosopher H. Paul Grice in 1975, are based on the Cooperative Principle, which outlines how individuals communicate effectively by adhering to four maxims: Quantity, Quality, Relation, and Manner. This study analyzed the Psick Show podcast scene “Asking BTS RM on 2022 Income Tax” using a descriptive qualitative method. The analysis identified 19 instances of flouting conversational maxims, comprising 5 utterances flouting the maxim of quality (26.32%), 4 flouting the maxim of quantity (21.05%), 4 flouting the maxim of relation (21.05%), and 6 flouting the maxim of manner (31.58%). The maxim of manner was the most frequently flouted, attributed to the speakers’ intentional use of ambiguous or indirect responses to create humor, evade sensitive topics such as income tax, or shift the conversation, particularly in the dynamic and playful interaction involving RM and the hosts. This study aims to enhance readers’ understanding of Grice’s conversational maxims and their flouting, offering insights into how intentional violations shape communication in the context of popular media such as podcasts.